The Undernutrition Prevalence of Under-Two-Years Infant in Indonesia: Do breastfeeding Practices Ecologically Matter? - Fandaruzzahra Putri Perdani; Agung Dwi Laksono; Djazuly Chalidyanto (Indian Journal of Forensic Medicine & Toxicology, 2021)
Undernutrition due to inappropriate feeding practices for children increases morbidity. Breastfeeding isconsidered the most important in a baby's growth and development. Breastfeeding started within one hour ofbirth and was maintained exclusively for the first six months until one year of age or more to obtain optimalbenefits. The study aims to determine the ecological relationship between undernutrition in 2-year-old infantand breastfeeding practice in Indonesia. This study is based on environmental analysis using a report of the2018 Indonesia Basic Health Survey. The dependent variable was the prevalence of undernutrition in 2-yearoldinfant. Besides, the independent variables were four optimum breastfeeding practices. The analysisused bivariate analysis with scatter plot in statistic application. The study results show . The higher theproportion of early initiation of breastfeeding in a province, the lower the levels of undernutrition in childrenaged two years in that province. The higher the ratio of starting to breastfeed less than one hour in an area,the lower the undernutrition levels in children aged two years in that area. On the other side, the higher theproportion of the mother giving all colostrum in a province, the lower the undernutrition levels in childrenaged two years in Indonesia in that province. The higher the proportion of still being breastfed 0-23 monthsin a region, the lower the undernutrition levels in children aged two years in that region. The study concludedthat optimal breastfeeding practices negatively affect the levels of undernutrition in children aged two years.